Epithelial-Myoepithelial Carcinoma of the Lacrimal Gland - Case Report and Review of Literature - Mara Augustine S. Galang MD; Gary John V. Mercado MD; Armida L. Suller-Pansacola MD; Jose M. Carnate Jr. MD (Philippine Journal of Ophthalmology)
Objective: To describe the clinicopathologic features and outcome of a patient with epithelial-myoepithelial carcinoma of the lacrimal gland who underwent modified lateral orbitotomy with en toto removal of the lesion and adjuvant radiotherapy.